Flood protection on the Odra river in the segment between Nowa Sól and Cigacice = Zabezpieczenie przeciwpowodziowe Odry na odcinku Nowa Sól-Cigacice - Hudak, Magda; Karczmar, Czesław; Kołodziejczyk, Urszula; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Existing river valley development methods which have been used for a significant period of time, as well as the use of land for construction of residential developments, have led to negative consequences for the environment. The agricultural use of land and its protection with hydraulic structures has restricted the natural flood area of the river.
Keywords: flood protection; dry polder; flood polders; ochrona przeciwpowodziowa; suche poldery; polder zalewowy